Intergovernmentalism and its implications – new institutional leadership in major EU reforms. Issue 8 (2nd August 2020) - Smeets, Sandrino; Beach, Derek
ABSTRACT: This paper contributes to a new understanding of the role and influence of the EU institutions in dealing with major EU reforms. Many have argued that, due to successive crises, Eurozone, Refugee and Brexit, EU decision making has become more intergovernmental. The role of the main intergovernmental body, the European Council, has been enhanced. Moreover, at various moments during these crises, the political leaders chose to by-pass the Community framework, and opt for intergovernmental solutions. However, in the literature, intergovernmentalism also refers to a dominance of the member states vis-à-vis the institutions in shaping these agreements. This paper looks at the process-level implications of this increased intergovernmentalism. We analyse and compare the role and influence of the institutions in five major reform negotiations: EFSF/ESM, Fiscal Compact, banking union, EU-Turkey deal and British renegotiation. An exploration of these empirical micro-foundations reveals more institution-driven processes and outcomes than the label intergovernmentalist suggests.